2012
DOI: 10.9790/3008-0211317
|View full text |Cite
|
Sign up to set email alerts
|

Change In Proximate Composition And Microbial Count By Low Temperaturepreservation In Fish Muscle Of Labeo Rohita(HamBuch)

Abstract: Abstract:The study was designed to investigate the effect of low temperature preservation on the chemical and microbial profile of fish muscle (Labeo rohita) stored for a period of twenty one days. The proximate composition and microbiological analyses were carried out at 7 days interval on muscle of fish during frozen storage. It was found that the protein, lipid, moisture and ash contents decreased significantly (P < 0.05) during the entire storage period. In fresh (unfrozen) day. Thus, a significant quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
10
37
1
1
Order By: Relevance
“…A significant fungal growth was recorded after 4the month of storage and this may be due to increase in aw, moisture content and salt content. Products deteriorate by growth of moulds if the water content is approximately 15% (Gandotra et al, 2012). These observations were in close agreement to the present study.…”
Section: Pathogenic Bacteriasupporting
confidence: 93%
“…A significant fungal growth was recorded after 4the month of storage and this may be due to increase in aw, moisture content and salt content. Products deteriorate by growth of moulds if the water content is approximately 15% (Gandotra et al, 2012). These observations were in close agreement to the present study.…”
Section: Pathogenic Bacteriasupporting
confidence: 93%
“…After nine months, a significant (P < 0.05) decrease in pH to 6.22 ± 0.10 was observed. Gandotra et al (2012) investigated the effect of low temperature (-12±2°C) preservation on the chemical and microbial profile of fish muscle (Labeorohita). The study result revealed that-the proximate composition decreased significantly (P < 0.05) and the microbial count increased gradually throughout the storage period.…”
Section: Discussionmentioning
confidence: 99%
“…According to Laycock & Reigier (1970), the acceptable limit of TBC is 1.0×10 7 cfu/g in fish sample. According to the above statement all the samples showed acceptable limit of TBC both at 0 0 and 4 0 C. Same increasing trend of bacterial count was also reported by Gandotra et al (2012a) The total mould count (TMC) was significantly lower than total bacterial count (TBC). The numbers of mould colonies were found only upto 7 days both at 0 0 and 4 0 C. It was found that total mould count gradually declined in all samples and this count was lowest in irradiated sample compare to other two samples (Table 2).…”
Section: Resultsmentioning
confidence: 59%